Speed of psychomotor reactions of pupils of the vocational rehabilitation training centre - Mockevičienė, Daiva; Dobrovolskytė, Ilona; Žukauskaitė, Renata (Social Welfare: Interdisciplinary Approach, 2013)
The aim of the research is to assess the change of psychomotor reactions of persons having intellectual disorders by applying individual programmes for development of physical abilities. 12 individuals with mild intellectual disorders and 13 individuals with moderate intellectual disorders who attend the vocational rehabilitation training centre participated in the research. The research was carried out on the ground of linear experiment methods. Assessment of the psychomotor reactions speed was carried out using hardware and software Ergos II Work Simulator. After the fi rst assessment, individual programmes for development of physical abilities have been designed and applied; the main aim of the programmes was to develop psychomotor reactions of people with intellectual disorders by applying physical exercises.